2017
DOI: 10.18203/2320-1770.ijrcog20175869
|View full text |Cite
|
Sign up to set email alerts
|

The effect of baseline serum luteinizing hormone levels on follicular development, ovulation, conception and pregnancy outcome in infertile patients with polycystic ovarian syndrome

Abstract: INTRODUCTIONPolycystic Ovarian Syndrome (PCOS) is the most common endocrine disorder in infertile women. Infertility affects 40% of women with PCOS.1 Polycystic ovary syndrome (PCOS), a relatively common reproductive endocrine disorder often associated with high endogenous LH secretion, menstrual cycle disorders, infertility and high rates of spontaneous abortion, was considered the paradigm condition that proved the potential untoward actions of LH.Raised tonic levels of luteinizing hormone (LH) is one of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
5
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 14 publications
3
5
1
Order By: Relevance
“…In the present study, on laparoscopic evaluation, majority of the patients had polycystic ovaries (31.1%), followed by tubal pathology (11.1%) and endometriosis, since PCOS is the most common cause of infertility in recent years. 17 The findings of our study are comparable to various other studies. [9][10][11][12][18][19][20][21] The prospective study by Boricha et al, in 50 infertile couples found polycystic ovarian syndrome as the commonest cause of infertility in both primary and secondary infertility.…”
Section: Discussionsupporting
confidence: 92%
“…In the present study, on laparoscopic evaluation, majority of the patients had polycystic ovaries (31.1%), followed by tubal pathology (11.1%) and endometriosis, since PCOS is the most common cause of infertility in recent years. 17 The findings of our study are comparable to various other studies. [9][10][11][12][18][19][20][21] The prospective study by Boricha et al, in 50 infertile couples found polycystic ovarian syndrome as the commonest cause of infertility in both primary and secondary infertility.…”
Section: Discussionsupporting
confidence: 92%
“…31 The mean LH value in the study is 5.9 IU/L which is comparable to a study done by Shanmugam et al where the mean LH value is 5.6 IU/L. 32 The incidence of cardiometabolic risk factors increase in women with polycystic ovarian syndrome. 33…”
Section: Discussionsupporting
confidence: 71%
“…Undue raised LH appears to have adverse effects on the pregnancy outcome. [ 10 11 12 13 ] Escalated production of androgens associated with high LH concentrations, along with their ineffectual aromatization to estrogens related to the low FSH levels in PCOS patients, leads to local androgen surplus and estrogen shortfall within the ovary. [ 14 ] It accounts for a potent androgenic domain for the follicle which halts the follicular growth.…”
Section: Discussionmentioning
confidence: 99%
“…This results in chronic anovulation in patients with PCOS, which forms the basis for the cause of infertility. [ 10 ]…”
Section: Discussionmentioning
confidence: 99%